Improvement of Social Moral Education from the Perspective of Tafsir Al Ibriz by Bisri Mustofa - Zayyadi, Ach.; Sholichah, Farhatus (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
Social morality plays a central role in shaping a harmonious, civilised, and inclusive society. This article aims to examine how social moral values are understood and developed through Bisri Mustofa's Tafsir Al-Ibriz and how it is relevant to improving the quality of moral education in Indonesia. Tafsir Al-Ibriz was selected due to its closeness to local culture and its practical approach in grounding the teachings of the Qur'an. The research method employed is qualitative literature review using content analysis. The results of this study are expected to provide conceptual and practical contributions in integrating Islamic-based social moral values into the national education system, in order to create a generation that is character-building, tolerant, and competitive. This article examines in depth the social moral interpretation in Bisri Mustofa's Tafsir Al-Ibriz of several verses of the Qur'an, namely QS. Al-Ahzab verses 70–71, QS. An-Nisa’ verse 135, and QS. Al-Hujurat verse 11. The results of the study indicate that Bisri Mustofa emphasises three main values: taqwa, justice, and tolerance. Taqwa is understood as active awareness in every action, justice as a universal principle that must be upheld even if it conflicts with personal interests, and tolerance as a crucial foundation for building healthy and mutually respectful social relationships.